Segurança de bioinseticida a base de Beauveria bassiana para a abelha sem ferrão Scaptotrigona postica (Hymenoptera: Apidae, Meliponini) - Silva, Camila Aparecida (Universidade Federal de São Carlos, 2023)
Brazil is currently home to 259 species of stingless bees, including Scaptotrigona postica, known locally as black mandaguari. This species plays a crucial role in the pollination of crops. However, it faces threats due to exposure to pesticides. The use of the fungus Beauveria bassiana for biological control has gained prominence seeking more sustainable agricultural practices although its safety for bees is not yet fully understood. This study focused on evaluating the safety of the B. bassiana-based bioinsecticide on adult S. postica bees. The main objective was to determine the median lethal dose (LD50) and the median lethal concentration (LC50) of the bioinsecticide at different concentrations by topical and oral exposure, being validated by a positive control, the pesticide dimethoate, and verify and compare the viability and presence of viable conidia with data from the manufacturer using microbiological techniques. Statistical analyses employed a generalized binomial model to construct dose-response curves and non-parametric tests to assess the significance of concentrations in the negative control. Toxicity was more pronounced at a concentration of 20 µg/µL, being 100 times higher than that in the field, both through contact and ingestion, evidencing a correlation between concentration and probability of mortality. The estimated LD50 of B. bassiana for S. postica was 2.3900 µg/µL, 11.95 times higher than the field dose. Similarly, LC50 was 2.9736 µg a.i./bee, 14.87 times higher than the field concentration of 0.2 µg/µL. The formulated bioinsecticide demonstrated high viability in a nutrient medium, guaranteeing its quality. The results suggest the possibility of defining safe levels for non-target organisms although higher concentrations of the B. bassiana-based commercial product present higher toxicity. It is fundamental to promoting agricultural sustainability and the preservation of bees, which are essential for healthy ecosystems and food security.
Safety of Beauveria bassiana-based bioinsecticide for the stingless bee Scaptotrigona postica (Hymenoptera: Apidae, Meliponini)
Keywords: Meliponini; Fungo entomopatogênico; Avaliações de risco; Entomopathogenic fungus; Risk assessments; CIENCIAS BIOLOGICAS::MICROBIOLOGIA